High BMI and male sex as risk factor for increased short-term renal impairment in living kidney donors – Retrospective analysis of 289 consecutive cases. (October 2017) - Unger, Lukas W.; Feka, Joy; Sabler, Philipp; Rasoul-Rockenschaub, Susanne; Györi, Georg; Hofmann, Michael; Schwarz, Christoph; Soliman, Thomas; Böhmig, Georg; Kainz, Alexander; Salat, Andreas; Berlakovich, Gabriela A.
Abstract: Background: Kidney transplantation represents the treatment of choice for end-stage renal disease (ESRD). However, nephrectomy bears certain short- as well as long-term risks for the healthy, voluntary donor. As obesity is increasing and is a known risk factor for surgical complications, we wanted to assess the impact of BMI on perioperative complication rates and renal function. Materials and methods: We retrospectively assessed patients undergoing living donor kidney nephrectomy at our institution. We identified 289 donors that underwent unilateral nephrectomy between January 2006 and December 2015. Donors were categorized according to their BMI (BMI <25 kg/m 2, BMI ≥25/<30 kg/m 2, BMI ≥30 kg/m 2 ). Where indicated, analysis of variance (ANOVA) was used to compare groups, a stepwise linear regression model was used to assess impact of BMI on the change of eGFR. Results: 126 donors (43.6%) had a BMI <25 while 120 (41.5%) had a BMI ≥25/<30 and 43 (14.9%) were obese with a BMI ≥30. BMI had no statistically significant influence on the percentage of laparoscopic approach (86.5% vs. 83.3% vs. 88.4%, p = 0.6564), on conversion rates (0% vs. 2.0% vs. 2.6%, p = 0.2879) or postoperative complication rates defined as Clavien Dindo ≥ II (8.7% vs. 13.3% vs. 14.0%, respectively; p = 0.4474). Notably, there were no Grade III or higher complications in any group. There was no difference in pre-operative kidney function, postoperative surgical site infection or systemic infection. BMI and male sex had a statistically significant influence on short-term decline of eGFR. Conclusion: Obese donors do not suffer from an increased risk of intraoperative or perioperative complication rates. However, male sex and high BMI are associated with a more pronounced short-term decline in renal function. The impact of BMI on long-term consequences for kidney donors needs to be defined in larger prospective cohorts. Highlights: Laparoscopic donor nephrectomy is safe in obese living kidney donors. Conversion rates are low in living kidney donation, irrespective of BMI. eGFR significantly decreases after unilateral donor nephrectomy during the first postoperative week. High BMI and male sex contribute to a more pronounced decline of eGFR during short-term follow-up.